Financial Crisis, Politically Connected CEOs, and the Performance of State-Owned Enterprises: Evidence from Korea. Issue 9 (1st September 2016) - Yu, Seungwon; Lee, Namryoung
ABSTRACT: This study examines under specific situations the performance of state-owned enterprises (SOEs) from two points of view—business performance and public performance. We find that SOEs with a politically connected CEO perform well even during a financial crisis as the SOEs are able to obtain more favorable treatment. However, the results imply that politically connected CEOs perform poorly when government subsidies are excluded as they may lack the skills for successful management. The results also confirm that SOEs encourage more corporate social responsibility (CSR) activities during a financial crisis in an effort to gain legitimacy by demonstrating that they are committed to social responsibility. However, politically connected CEOs have a negative effect on CSR performance during a financial crisis.